Integrasi Metode Gravitasi dan Metode Perbandingan Eksponensial untuk Penentuan Pusat Distribusi Pangan di Kabupaten Halmahera Selatan - Syamsul Bahri; Sutrisno Suro Mardjan; Emmy Darmawati; Bambang Pramudya (Jurnal Keteknikan Pertanian, 2020)
AbstractThis study aims to determine the location of distribution centers in each islandgroup in South Halmahera Regency. Data sources were obtained from survey resultsand literature studies. Integration of Gravity Models and Exponential ComparisonMethods are used to determine the best location. Subdistrict of Kayoa as the locationof distribution centers for Kayoa-Makian islands group, Subdistrict of West Gane forGane islands group, Subdistrict of Bacan for Bacan-Kasiruta islands group, and theObi Subdistrict for Obi Islands group. The location chosen as the distribution centerin each island group is a main subdistrict which physically has better resourcecarrying capacity.